Obstetrician-gynecologists' knowledge, attitudes and practices regarding major depressive disorder. (March 2013) - Fuller, Elizabeth; Anderson, Britta; Leddy, Meaghan; Schulkin, Jay
Abstract: Background : Obstetrician-gynecologists (ob-gyns) provide depression screening and treatment, but these practices could be improved. This study investigated the use of depression screening tools and treatment of adolescents with depressive symptoms. Methods : Surveys were sent to 220 members of the American College of Obstetricians and Gynecologists (ACOG) who had responded to a survey on depression in the past two years. Response rate was 66% ( n = 145). Questions included those related to standardized depression screening, antidepressant prescribing behavior, use of the Diagnostic and Statistical Manual of Mental Disorders-Fourth Edition (DSM-IV) and knowledge of adolescent depression. Results : A total of 40% use standardized screening tools for depression with 46% using the Beck Depression Inventory-II and only 5% using the Patient Health Questionnaire-2 (PHQ-2). The majority (89%) of ob-gyns do not employ the DSM-IV to confirm a diagnosis of major depressive disorder. Of the ob-gyns indicating treating depression with antidepressants, 97% prescribe selective serotonin reuptake inhibitors. Only 19 respondents do not prescribe antidepressants, and instead refer depressed patients to mental health specialists. Most (79%) ob-gyns identified sexual problems as the primary side effect deterring prescribing of antidepressant medication. Ob-gyns were fairly accurate at estimating the prevalence of adolescent depression. Conclusion : Ob-gyns are not utilizing the recommended validated resources such as the DSM-IV or PHQ-2 for diagnosis of depression or prior to prescribing antidepressants.